If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + (n + -1) + -4 = 0 Reorder the terms: 11 + (-1 + n) + -4 = 0 Remove parenthesis around (-1 + n) 11 + -1 + n + -4 = 0 Reorder the terms: 11 + -1 + -4 + n = 0 Combine like terms: 11 + -1 = 10 10 + -4 + n = 0 Combine like terms: 10 + -4 = 6 6 + n = 0 Solving 6 + n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + n = 0 + -6 Combine like terms: 6 + -6 = 0 0 + n = 0 + -6 n = 0 + -6 Combine like terms: 0 + -6 = -6 n = -6 Simplifying n = -6
| 7*-2-3*7=11 | | 12h-5=11h+5-r | | 4n-7+n-1=2n+19 | | 45x-25x=0 | | 3p-7n=p | | 5+7b=-2 | | 7*5-3*8=11 | | y+3=5(x-7) | | 7*0-3*-4=11 | | (3x-7)2+5(2x+1)(x-2)=-x^2-[-(3x+1)] | | x-15=8x+6 | | -2(w+4)=w-5+3(4w+1) | | 3xty=32 | | 5.25-0.75a=5.25+0.75a | | 5.25-0.75a=5.25+0.75 | | 5*-4+2*-6=-1 | | -3x-3(6x+6)=-18+4x | | 7x^2+28x+63=0 | | 5*1+2*-3=-1 | | 17-5m=50+3m | | 14y^2-23y+9= | | 5*2+2*8=-1 | | -12x+14=12x-82 | | -4y-1=21.75 | | 0.8x+4=0 | | .40C+(.50)(500-C)=220.00 | | 55=75+1-25 | | -3.8n+4=4.4n-37 | | 5*-3+2*7=-1 | | 22+2x=x | | -96=-4(6+3x) | | 5x=49 |